LEGUME INDIAN BEAN (PHASEOLUS VULGARIS) PARTIALLY PURIFIED ANTI-NUTRITIONAL PROTEIN FACTOR EXHIBIT ANTI-OXIDANT, IMMUNOMODULATORY AND ANTI-CANCER PROPERTIES - AVALAPPA, HEMAVATHI; PADIYAPPA, SHRUTHISHREE D.; PATHAPPA, NIRANJANA; BETTADATUNGA, PRABHAKAR T.; PRAMOD, SIDDANAKOPPALU N. (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: This study was aimed to access one of the hidden ANF in Indian bean and assessment of its antioxidant, immunomodulatory, antiangiogenic, and anti-cancer properties. Methods: Indian beans were processed and evaluated for the presence of ANF through HA activity. Bean-ANF was partially purified by ammonium sulfate precipitation (ASP) and dialysis. Obtained Partially Purified bean-ANF (PPb-ANF) resolved on 12% SDS-PAGE, analyzed protease digestibility. The immunogenicity of PPb-ANF was characterized by producing polyclonal antibodies and checked for the presence of natural antibodies in healthy human sera. Pharmacological studies of PPb-ANF were assessed through anti-oxidant, immunogenic, anti-angiogenic and anti-cancer assays. Results: Partially purified Bean-ANF (PPb-ANF) showed significant specific HA activity up to 150 Units/mg compared to crude extract 9.3 of Units/mg. The PPb-ANF was identified to have more than 90% homogeneity in purity with an observed M W of 30-32 kDa. PPb-ANF showed significant pepsin digestive stability up to 2 h at 37 ᵒC and appears digestive resistant. Rabbit produced anti-PPb-ANF IgG polyclonal antibody on immunization and exhibited immunogenic properties. Natural human IgG and IgE antibodies were found in the non-atopic human sera against PPb-ANF, indicative of its immunogenicity. Pharmacological studies of PPb-ANF confirmed its potent antioxidant activity. At 400 µg of PPb-ANF showed the highest around 90% DPPH activity and at 150 µg of PPb-ANF showed 89% inhibitory lipid peroxidation activity. The PPb-ANF showed 70% (3 μg) and 40% (1.5 μg) inhibitory in blood vessel density compared to control and exhibited significant anti-angiogenic activity. The PPb-ANF showed a significant (*p<0.05.) reduction in solid tumor weight upon dose-2 treatment (50 mg/kg body weight) and also increased lifespan up to 70 d compared with the control tumor model. Conclusion: PPb-ANF was identified as digestive-resistant, hemagglutinin with a molecular weight of 30-32 kDa. The protein is immunogenic and has potential antioxidant, antiangiogenic and anti-cancer properties. Further purification and mechanistic-based pharmacological characterization might explore this protein as a potential anti-cancer molecule.